2021
DOI: 10.3390/ijms222413290
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Bearing Multiple Post-Translational Modifications as Antigenic Targets for Severe Rheumatoid Arthritis Patients

Abstract: Rheumatoid arthritis (RA) is characterized by the presence of autoantibodies that are of paramount importance for the diagnosis and prognosis of the disease and have been implicated in its pathogenesis. Proteins resulting from post-translational modifications (PTMs) are capable of triggering autoimmune responses important for the development of RA. In this work, we investigate serum antibody reactivity in patients with an established RA against a panel of chimeric peptides derived from fibrin and filaggrin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…For the first time, we described a novel peptide-based antigen bearing citrulline, homocitrulline and acetyl-lysine into the same peptide sequence to consistently detect severe phenotypes in CFFCHAP positive RA patients. We demonstrated an association between the presence and levels of AMPA titers and severe manifestations of RA such as joint destruction and ILD [5].…”
Section: Fig 1 Chemical Structures Of Relevant Ptms In Ra Citrulline ...mentioning
confidence: 68%
“…For the first time, we described a novel peptide-based antigen bearing citrulline, homocitrulline and acetyl-lysine into the same peptide sequence to consistently detect severe phenotypes in CFFCHAP positive RA patients. We demonstrated an association between the presence and levels of AMPA titers and severe manifestations of RA such as joint destruction and ILD [5].…”
Section: Fig 1 Chemical Structures Of Relevant Ptms In Ra Citrulline ...mentioning
confidence: 68%
“…Synthetic peptides mimicking post-translationally modified autoantigens have been successfully used for the development of specific in vitro diagnostic/prognostic assays of autoimmune diseases, including SLE [ 125 ]. Moreover, the use of post-translationally modified peptides has allowed identification of autoantibodies associated with the most severe phenotypes [ 126 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In the same line, Niijar et al [105] recently reported that the optimal prediction of erosive radiographic progression in patients with new-onset RA requires study of the effect of AMPA combinations. Considering that the overlap between the three families of autoantibodies (ACPAs, anti-CarP and anti-APA) is characteristic of RA, novel peptide-based antigens bearing citrulline, homocitrulline and/or acetyl-lysine were designed to further study the role of AM-PAs as biomarkers linked to the presence of ILD as well as the severity of joint destruction [116]. Based on the previously defined synthetic peptide structures (CFFCP1 and CFFHP), three novel citrullinated/homocitrullinated (CFFCHP1, CFFCHP2 and CFFCHP3) and one citrullinated/homocitrullinated/acetylated (CFFCHAP) chimeric peptides were synthesized by SPPS preserving the citrulline at the 630 position of the α-fibrin (617-631) domain, taking into account the important role of this specific position for autoantibody binding that was previously reported [83,86].…”
Section: Synthetic Post-translationally Modified Peptides For the Spe...mentioning
confidence: 99%
“…To the best of our knowledge, in Ref. [116] is reported for the first time in the litera- To the best of our knowledge, in Ref. [116] is reported for the first time in the literature a peptide that simultaneously contains the three most relevant PTMs for RA at specific positions of their unique primary structure as an antigenic target of the autoantibodies associated with severe clinical phenotypes of RA.…”
Section: Synthetic Post-translationally Modified Peptides For the Spe...mentioning
confidence: 99%